Mathematics subject teacher training at the University of Helsinki - Terhi Hautala; Oikkonen Juha (LUMAT, 2015)
This paper describes the structure and the role of the mathematics teacher education at the Department of Mathematics and Statistics of the University of Helsinki. The article describes how innovations and research in university math education can lead to better teacher education.